Mímesis, performance, representação: o uso das máscaras na Amazônia - Tassi Teixeira, Rafael (’Ilu. Revista de Ciencias de las Religiones, 2005)
This paper tries to conceptualize the use of masks for the creation of a synestetic and transformation effect on the imaginative and symbolic art of repercutive some landscape of distance and familiarity in which the ‘other’ visualizes a diagram of effects and representations of masks in ritual art of amazonia. This study, far from being a material description of cultures and the use of masks, tries to explore why his utilization, as seen as the manipulation of powers and the intense dramaticity with the act of masking on the ritual performance in the brazilian amazon. The principal focus will be the constance of the creation of the identity-alterity in which the mythological figures, reveal experiences in collective dreams and the theater of being constitute the ‘ritual person’ that enfatize the long universe of an outfit of forest in the symbolic confection of masks and his multisignifities. Finally, we try to explore the idea of performance behind the amazon cenografic look and the use of masks, adornment and ornaments to the construction of body and person, and identity in the geography of souls for the people of the Amazon.